3D Airway changes using cone beam computed tomography in patients following mandibular advancement surgery with and without constriction. (10th May 2019) - Furche, Silja; Edwards, Sean P.; Aronovich, Sharon; Hummon, Gregory; Shah, Kanchi B.; Conley, R. Scott
Structured Abstract: Objectives: The aim of this study was to compare three‐dimensional airway changes resulting from mandibular advancement surgery and mandibular advancement surgery with constriction. Setting and Sample Population: The University of Michigan School of Dentistry and Medical Center. A total of 42 patients undergoing mandibular advancement with or without simultaneous constriction. Materials and Methods: A retrospective airway evaluation of patients undergoing mandibular advancement with or without simultaneous mandibular constriction was performed. Cross‐sectional evaluation at standardized locations, minimum cross section and volumetric analysis were performed using Dolphin Imaging TM Version 11.7. Results: Patients undergoing mandibular advancement with or without constriction experienced significant airway increases ( P < 0.05). Patients who underwent mandibular advancement only gained nearly twice as much airway volume as mandibular advancement with simultaneous constriction (8.69 mm 3 vs 4.3 mm 3 ). The largest increase for both groups was observed in the minimum axial area in the oropharynx segment (119.5 mm 2 ) and the axial area of the retroglossal region (137.2 mm 2 ). Conclusions: The findings demonstrate mandibular advancement with constriction results in airway enlargement following surgery.